2020
DOI: 10.1364/prj.391160
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity, high-spatial-resolution distributed strain sensing based on a poly(methyl methacrylate) chirped fiber Bragg grating

Abstract: In this study, a high-sensitivity, high-spatial-resolution distributed strain-sensing approach based on a poly(methyl methacrylate) chirped fiber Bragg grating (CFBG) is proposed and experimentally demonstrated. Linearly chirped FBGs in a polymer optical fiber provide an alternative to the silica fiber owing to the lower Young’s modulus, which can yield a higher stress sensitivity under the same external force. According to the spatial wavelength-encoded characteristic of the CFBG, a fully distributed strain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The grating device has been placed close to the radiofrequency applicator, which have one tip inserted in situ of the target. The reflection spectrum of the chirped Also, a high spatial resolution distributed strain sensing approach based on Chirped POF FBG was reported by researchers in China [66], through spatial wavelength encoded characteristic of Chirped POF FBG, a fully distributed high resolution strain measurement can be achieved by optical frequency domain reflectometry method, which is a promising approach for short-range fully distributed sensing systems, schematic of the experiment setup shown in Figure 12.…”
Section: Applications Of Pof Grating Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The grating device has been placed close to the radiofrequency applicator, which have one tip inserted in situ of the target. The reflection spectrum of the chirped Also, a high spatial resolution distributed strain sensing approach based on Chirped POF FBG was reported by researchers in China [66], through spatial wavelength encoded characteristic of Chirped POF FBG, a fully distributed high resolution strain measurement can be achieved by optical frequency domain reflectometry method, which is a promising approach for short-range fully distributed sensing systems, schematic of the experiment setup shown in Figure 12.…”
Section: Applications Of Pof Grating Devicesmentioning
confidence: 99%
“…The authors declare no conflict of interest. Schematic of the experiment setup for fully distributed strain measurement [66]. Fabrication…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Lyu et al demonstrated a polymethylmethacrylate and chirped fiber Bragg grating (FBG)-based strain sensor, which showed a spatial resolution of 1 mm across a gauge length of 40 mm. [46] Using carbon-encapsulated Fe 3 O 4 nanoparticles embedded in a soft copolymer, Hong et al created a high-performance MC-based strain sensor that demonstrates a dynamic color change from purple to red with a spatial resolution of 100 µm, [47] substantially enhanced the minimal resolvable area when compared with the optical solutions. For the ML-based strain sensor, Wu et al demonstrated a ZMPs-based device that can detect an area as small as 100 µm (254 dpi) with fast response.…”
Section: Spatial Resolutionmentioning
confidence: 99%
“…Lyu et al demonstrated a polymethylmethacrylate and chirped fiber Bragg grating (FBG)‐based strain sensor, which showed a spatial resolution of 1 mm across a gauge length of 40 mm. [ 46 ]…”
Section: Characteristicsmentioning
confidence: 99%
“…In the past few decades, due to high performance and simple manufacturing steps of photonic sensors, people have displayed increasing interest in photonic sense solutions [1][2][3][4]. Recently, optical technology was developed, which improves the detection limit as well as the sensitivity and the selectivity of biosensors.…”
Section: Introductionmentioning
confidence: 99%